Factors associated with the preference of institutional delivery after antenatal care attendance in Northwest Ethiopia - Araya Mesfin Nigatu; Kassahun Alemu Gelaye (BMC, 2019)
Abstract Background Even though maternal mortality during the time of delivery can be prevented with proper medical care in the health facilities with skilled healthcare professionals, unexpectedly death is still high and is a persistent challenge for low-income countries. Therefore identifying factors affecting the preference of institutional delivery after antenatal care service attendance is a key intervention to reduce maternal morbidity and mortality. Method A community-based cross-sectional study was conducted using face to face using interviewer-administered questionnaire from a total of 528 women who gave their last birth within 12 months prior to the study period who attended antenatal care (ANC) services. Descriptive statistics, bivariable and multivariable logistic regressions analysis were performed. Statistical significance was considered at p < 0.05 and odds ratio with 95% CI were calculated to examine factors associated with institutional delivery. Results Of the 528 pregnant women attending ANC services, 250 (47.3%) gave birth in health facilities (95% CI: 43.2, 51.7%). Urban residence [AOR = 7.8, 95% CI: 4.1, 15.6], four or more ANC visits [AOR = 4.5, 95% CI: 1.6, 12.3], those who got health education on ANC [AOR = 2.9, 95% CI: 1.5, 5.6] and decision on place of delivery with her partner agreement [AOR = 3.3, 95% CI: 1.3, 8.7] were found to be contributing factors for the preference of institutional delivery. Conclusion Institutional delivery was not adequate. Residence, number of antenatal care visits, health education, decisions making on a place of delivery and having awareness of the difference of place of delivery were contributing factors for the preference of institutional delivery.